Functionalised cyclodextrin-based metal–organic frameworks. Issue 54 (21st June 2017) - Hartlieb, K. J.; Peters, A. W.; Wang, T. C.; Deria, P.; Farha, O. K.; Hupp, J. T.; Stoddart, J. F.
Abstract : A CD-MOF is prepared from amino-functionalized (blue moon) γ-CD, which permanently captures CO2 as a carbamate (red moon). Abstract : CD-MOF, an extended framework incorporating the C 8 symmetric cyclic oligosaccharide, γ-cyclodextrin (γ-CD), is based on the coordination of alkali metal cations to alternating α-1, 4-linkedd -glucopyranosyl units on the primary and secondary faces of the γ-CD tori. Here, we report the synthesis and characterisation of an amino-functionalised CD-MOF that is isostructural with pristine CD-MOF and adsorbs CO2 permanently.